Pikukuh Tilu of Sunda Wiwitan: From Philosophy to Pragmatism of Digital Educational Leadership in Educational Management - Wiryadinata, Halim; Nadeak, Bernadetha (Universitas Ahmad Dahlan, 2025)
This research examines how the Indonesian religious practice, Sunda Wiwitan’s philosophy, serves as a pragmatic approach to digital leadership in the education sector during the era of digitalization. Education becomes a commodity and penetrates the market through industrial interest in the era of technology. Therefore, the gap in education in the era of educational capitalism needs strong leadership in the digital era. This condition requires a local character to gain a demand for education as a commodity in economic capitalism. We argue that the character of Pikukuh Tilu—a balanced life—triggers the pragmatic act of digital educational leadership in the digital era. In accessing books, journals, academic writings, and historical documents as secondary sources, this study employs sociological methods to separate the historical Sunda Wiwitan, its development, and apply it in the research logically. The result of this study is that the Pikukuh Tilu philosophy teaches a dialectical dialogue between religious practice and digital educational leadership to adopt the character of balance in education. This research concludes that religious practice philosophy never abandons local character to exist in modern times.